SISTEM INFORMASI IKLIM BERBASIS SMS (SHORT MESSAGE SERVICE) BAGI PARA PETANI DI PERDESAAN - Lisnawanty Lisnawanty; Gusti Rendani Putri; Dewi Apriana (LPPM Universitas Bina Sarana Informatika, 2011)
In agricultural production, climate elements such as rainfall, humidity and sunlight becomes very important in increasing agricultural production. Climate change is caused by the increasing average temperature at the surface of the earth that cause changes in other climatic elements, such as increased sea surface temperatures, increased evaporation in the air, the changing patterns of rainfall, and air pressure patterns of global climate change. According to the Intergovernmental Panel on Climate Change (IPCC), climate change occurs gradually and is caused by human activity so the temperature of the earth getting warmer, and change dramatically influencing the increase in evaporation and evapotranspiration leading to the depletion of water availability. Climate change is also indicated by the unequal amount of water in the rainy season and dry season so that agricultural land prone to flooding during the rainy season and drought during the dry season. Climatic conditions is a major obstacle for farmers to maintain crop and even the possibility of crop failure. Therefore, an alternative solution is to farm the current pattern to follow weather patterns by changing the cropping pattern and commodities that will be planted according to climatic conditions and to save rain water. The system is designed utilizing SMS (Short Message Service) is expected to provide immediate information on local weather patterns that occur as well as the best cropping patterns. The farmers can specify what commodities to be grown in that season. So that crop failure is no longer expected to occur, the minimum can be reduced as possible. Keywords : Short Message Service, system, information, climate, realtime